Large Reduction in Postoperative Posterior Tibial Slope Risks Anterior Collapse of the Tibial Component in Fixed-Bearing Unicompartmental Knee Arthroplasty - Shingo Kurihara, MD; Kazuhisa Hatayama, MD, PhD; Masanori Terauchi, MD, PhD; Kenichi Saito, MD, PhD; Hiroshi Higuchi, MD, PhD; Hirotaka Chikuda, MD, PhD (Arthroplasty Today, 2022)
Background: Although the posterior tibial slope (PTS) of the tibial component in unicompartmental knee arthroplasty is recommended to be between 3° and 7°, variations in preoperative PTS are wide. The purpose of this study was to evaluate the influence of the changes in preoperative and postoperative PTS on clinical outcomes. Methods: One-hundred and eighty-two knees that underwent medial fixed-bearing unicompartmental knee arthroplasty were evaluated retrospectively. The mean follow-up period was 36.4 ± 13.2 months (range, 24 to 63 months). Preoperative and postoperative PTS were measured on lateral radiographs. Knees were classified in the large reduction group if the postoperative PTS was reduced by more than 5° compared with the preoperative value and in the small reduction group if not. Knee flexion angle and 2011 Knee Society Knee Scoring System were evaluated at the last follow-up of at least 2 years. Results: Thirty-three knees were classified in the large reduction group, and 149 knees were classified in the small reduction group. The preoperative and postoperative PTS of large and small reduction groups were 10.9 ± 2.2, 3.6 ± 2.4 degrees and 7.7 ± 2.7, 7.1 ± 2.4 degrees, respectively. Flexion angle and 2011 Knee Society Knee Scoring System were not significantly different between the groups. However, the incidence of anterior collapse of the tibial component in the large group was significantly higher than that in the other group (P < .001). Conclusions: Large reduction in the postoperative PTS may be associated with anterior tibial collapse, and therefore this study shows one potential benefit for matching native slope.